Effect of Ceramic Veneering on the Microstructure of Pre-sintered Cobalt-Chromium, Compared to Pre-sintered Zirconia and Conventional Cast Alloys - Elie E Daou; Mutlu Özcan; Pascale Salameh; Ziad Salameh (Tehran University of Medical Sciences, 2024)
Objectives: We aimed to evaluate ceramic-alloy interface and emphasize the alteration of alloy microstructure after ceramic layering. Materials and Methods: Thirty-two discs made from a ceramic-alloy combination of pre-sintered cobalt-chromium (CoCr), cast CoCr, cast nickel-chromium (NiCr), or pre-sintered zirconia were prepared with eight discs in each group. Four specimens were examined as manufactured and four were ceramic-layered. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-Ray diffractometer (XRD), and an atomic force microscope were used for analysis. Non-layered specimens received ceramic fire-heating without adding any ceramic. Alloy microstructure was compared before and after ceramic veneering or heating within the same group. Mean differences in grain size and surface roughness were compared among groups. P<0.05 was considered significant. Results: SEM showed a close bonding interface between alloys and ceramics. EDX demonstrated differences compared to the manufacturer's composition. Ceramic-layering reduced grain size for both milled alloys (P<0.05), whereas grain size increased in cast groups (P=0.011). Heat treatment did the same for the CoCr groups (P=0.013). Ceramic veneering increased the surface roughness of the cast CoCr (Gi) (P=0.029) and NiCr (Wi) (P=0.005) groups, whereas zirconia roughness average (Ra) showed a slight decrease (P=0.282). XRD showed no differences among zirconia, NiCr, and milled CoCr groups before and after veneering. Crystallite size differed between monoclinic and tetragonal phases in zirconia. Conclusion: The study highlights that ceramic-layering induces significant microstructural changes in alloys, enhancing bonding potential and mechanical stability. Pre-sintered materials show a fine homogeneous surface, optimizing ceramic adherence and potentially improving clinical outcomes.